Network modulation by the subthalamic nucleus in the treatment of Parkinson’s disease - Trošt, Maja (Neuroimage, 2006)
Deep brain stimulation of the subthalamic nucleus (STN DBS) has become an accepted tool for the treatment of Parkinson’s disease (PD). Although the precise mechanism of action of this intervention is unknown, its effectiveness has been attributed to the modulation of pathological network activity. We examined this notion using positron emission tomography (PET) to quantify stimulation-induced changes in the expression of a PD-related covariance pattern (PDRP) of regional metabolism. These metabolic changes were also compared with those observed in a similar cohort of patients undergoing STN lesioning. We found that PDRP activity declined significantly (P < 0.02) with STN stimulation. The degree of network modulation with DBS did not differ from that measured following lesioning (P = 0.58). Statistical parametric mapping (SPM) revealed that metabolic reductions in the internal globus pallidus (GPi) and caudal midbrain were common to both STN interventions (P < 0.01), although declines in GPi were more pronounced with lesion. By contrast, elevations in posterior parietal metabolism were common to the two procedures, albeit more pronounced with stimulation. These findings indicate that suppression of abnormal network activity is a feature of both STN stimulation and lesioning. Nonetheless, these two interventions may differ metabolically at a regional level.